Service included four-star secrets of an eavesdropping waiter - Damrosch, Phoebe 1978-
Damrosch, former waiter at the New York City restaurant Per Se, details her career as a waiter, describing the intimate workings of restaurant table service at its best. Tales of critics and celebrities spice up the memoir with a few tips on how to earn a waiter's respect sprinkled throughout.